Peripheral combination treatment of leptin and an SGLT2 inhibitor improved glucose metabolism in insulin-dependent diabetes mellitus mice - Hiroshi Yaginuma; Ryoichi Banno; Runan Sun; Keigo Taki; Akira Mizoguchi; Tomoko Kobayashi; Mariko Sugiyama; Taku Tsunekawa; Takeshi Onoue; Hiroshi Takagi; Daisuke Hagiwara; Yoshihiro Ito; et al. (Elsevier, 2021)
We investigated whether peripheral combination treatment of a sodium-glucose cotransporter 2 (SGLT2) inhibitor and leptin improves glucose metabolism in insulin-dependent diabetes mellitus (IDDM) model mice. Twelve-week-old male C57BL6 mice were intraperitoneally administered a high dose of streptozotocin to produce IDDM. IDDM mice were then divided into five groups: SGLT2 inhibitor treatment alone, leptin treatment alone, leptin and SGLT2 inhibitor co-treatment, untreated IDDM mice, and healthy mice groups. The blood glucose (BG) level at the end of the dark cycle was measured, and a glucose tolerance test (GTT) was performed and compared between the five groups. Leptin was peripherally administered at 20 μg/day using an osmotic pump, and an SGLT2 inhibitor, ipragliflozin, was orally administered at 3 mg/kg/day. Monotherapy with SGLT2 inhibitor or leptin significantly improved glucose metabolism in mice as evaluated by BG and GTT compared with the untreated group, whereas the co-treatment group with SGLT2 inhibitor and leptin further improved glucose metabolism as compared with the monotherapy group. Notably, glucose metabolism in the co-treatment group improved to the same level as that in the healthy mice group. Thus, peripheral combination treatment with leptin and SGLT2 inhibitor improved glucose metabolism in IDDM mice without the use of insulin.